The psychosocial environment and obstetric complications - Hererra, Julián A.; Gonzáles T., Marcela (Colombia Medica, 1987)
A total of 122 women were studied with premature labor or arterial y hypertension induced by pregnancy in the group of cases and normal pregnancies in the women of the control group. The level of stress and social support during pregnancy were examined, using Hamilton’s scale to evaluate the anxiety level and the scale of social readjustment, according to Holmes and Rahe, to evaluate the level of change in the events of life and the family Apgar of Smilkstein to evaluate the degree of familial dysfunction. High proportions of single mothers and undesired pregnancies were found in both groups, with a higher level of stress in pathological patients with a significant statistical difference (P < 0.01). The accumulation of stressful events and severe anxiety without adequate social support during pregnancy showed a significant answer dose with a relative risk of 3.85 to develop obstetric pathology when the patient is subject to a high level of stress. This risk increases to 10.3 when, at the same time, the patient is missing adequate social support for her pregnancy. These results should be taken into account when pregnant women are studied in a biopsychosocial profile.